Scribal habits in sixth-century greek purple codices - Hixson, Elijah (New Testament Tools, Studies and Documents, 2019)
In Scribal Habits in Sixth-Century Greek Purple Codices, Elijah Hixson assesses the extent to which unique readings reveal the tendencies of the scribes who produced three luxury manuscripts of Matthew's Gospel. The manuscripts, Codex Purpureus Petropolitanus (N 022), Codex Sinopensis (O 023) and Codex Rossanensis (Σ 042), were each copied in the sixth century from the same exemplar. Hixson compares the results of a modified singular readings method to the number of actual changes each scribe made. An edition of the lost exemplar and transcriptions of Matthew in each manuscript follow in the appendices. Of particular relevance to New Testament textual criticism is the observation that the singular readings method does not accurately reveal the habits of these three scribes.